Critical Role of CXCL16 in Hypertensive Kidney Injury and Fibrosis - Xia, Yunfeng (2013)
Recent evidence indicates that inflammation plays a critical role in the initiation and progression of hypertensive kidney disease. However, the signaling mechanisms underlying the induction of inflammation are poorly understood. We found that CXCL16 was induced in renal tubular epithelial cells in response to angiotensin II in a NF-κB-dependent manner. To determine if CXCL16 plays a role in angiotensin II-induced renal inflammation and fibrosis, wild-type and CXCL16 knockout mice were infused with angiotensin II at 1500 ng/kg/min for up to 4 weeks. Wild-type and CXCL16 knockout mice had comparable blood pressure at baseline. Angiotensin II treatment led to an increase in blood pressure that was similar between WT and CXCL16 knockout mice. CXCL16 knockout mice were protected from angiotensin II-induced renal dysfunction, proteinuria, and fibrosis. CXCL16 deficiency suppressed bone marrow-derived fibroblast accumulation and myofibroblast formation in the kidneys of angiotensin II-treated mice, which was associated with less expression of extracellular matrix proteins. Furthermore, CXCL16 deficiency inhibited infiltration of F4/80(+) macrophages and CD3(+) T cells in the kidneys of angiotensin II-treated mice compared with wild-type mice. Finally, CXCL16 deficiency reduced angiotensin II-induced proinflammatory cytokine expressions in the kidneys. Taken together, our results indicate that CXCL16 plays a pivotal role in the pathogenesis of angiotensin II-induced renal injury and fibrosis through regulation of macrophage and T cell infiltration and bone marrow-derived fibroblast accumulation.